Thermal insulation material and battery pack
By dispersing organic phase change materials in bacterial cellulose aerogel and modifying them with crosslinking agents, the problem of poor thermal insulation performance in the prior art is solved, significantly Improves the safety of the battery pack.
Patent Information
- Application Number
- CN202411470688.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the cellulose aerogel thermal insulation material in the battery pack has an unsatisfactory channel structure and limited mechanical properties, resulting in poor thermal insulation performance and affecting the safety of the battery pack.
By dispersing the organic phase change material in the bacterial cellulose aerogel and modifying the cellulose aerogel with a crosslinking agent, a heat insulating material with an ideal network structure and mechanical properties are formed. The material is prepared by a freeze-drying process to form a cellulose aerogel with an average pore size of 18 to 23 nm, and the organic phase change material is blocked into the holes of the cellulose aerogel by vacuum impregnation technology.
It significantly improves the pore size and mechanical properties of cellulose aerogel, improves the energy storage efficiency and mechanical strength of the thermal insulation material, can effectively absorb the heat generated by the battery cell, prevent heat from spreading, and improves the safety of the battery pack.
Smart Images

Figure CN119490824A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion battery manufacturing, and specifically relates to a thermal insulation material and a battery pack. Background Art
[0002] With the development of new energy vehicles, the use of lithium batteries is increasing day by day. A battery pack is often composed of hundreds of cells. Therefore, if a single cell has thermal runaway, it will often spread quickly to other cells, causing great safety hazards. At present, the industry mainly retains a certain gap between cells and uses aerogel as a buffer and thermal insulation material to fit the large surface of the cell. This is mainly because aerogel is a highly porous 3D nanostructured material with good properties such as high specific surface area, large porosity, low dielectric constant, low density and low thermal conductivity.
[0003] The aerogels currently used are mainly high polymer and silicon-based aerogels, and the combustion of the battery cells after loss of control often releases a large amount of toxic gases. Compared with these traditional materials, bacterial cellulose aerogel has great application prospects in the field of thermal insulation due to its rich pore structure, high porosity and low density. However, due to the excessive growth of ice crystals, the bacterial pure cellulose aerogel prepared by freeze-drying method usually presents less porous pore walls, less mesopores and micropores, and the bacterial cellulose is connected by hydrogen bonds, and the mechanical properties are insufficient, which limits its application.
[0004] Therefore, developing an aerogel thermal insulation material with ideal network structure and mechanical properties is a problem that needs to be solved at present. Summary of the invention
[0005] The present invention provides a thermal insulation material and a battery pack, aiming to solve the problem in the prior art that the cellulose aerogel thermal insulation material in the battery pack has an unsatisfactory pore structure and limited mechanical properties, resulting in poor thermal insulation performance and affecting the safety of the battery pack.
[0006] On the one hand, an embodiment of the present application provides a thermal insulation material, including a cellulose aerogel and an organic phase change material dispersed in the cellulose aerogel; wherein the cellulose aerogel is obtained by reacting bacterial cellulose with a cross-linking agent.
[0007] In some embodiments, the average pore size of the cellulose aerogel is 18-23 nm.
[0008] In some embodiments, the melting point of the organic phase change material is 10-20°C.
[0009] In some embodiments, the mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:3.
[0010] In some embodiments, the molecular weight of the bacterial cellulose is 50,000 to 2,000,000.
[0011] In some embodiments, the cross-linking agent includes at least one of glutaraldehyde, malondialdehyde, and glyoxal.
[0012] In some embodiments, the organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid, and stearic acid.
[0013] On the other hand, an embodiment of the present application further provides a method for preparing a thermal insulation material, which is used to prepare the thermal insulation material in any of the above embodiments, comprising the following steps:
[0014] Providing bacterial cellulose and a cross-linking agent, mixing, heating and reacting to obtain a homogenate;
[0015] freeze-drying the homogenate to obtain cellulose aerogel;
[0016] The cellulose aerogel is immersed in an organic phase change material liquid to obtain the thermal insulation material.
[0017] In some embodiments, the volume ratio of the bacterial cellulose slurry to the cross-linking agent is 50:(1-2.5).
[0018] In some embodiments, the mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:(2-5).
[0019] In some embodiments, the cross-linking agent includes at least one of glutaraldehyde, malondialdehyde, and glyoxal.
[0020] In some embodiments, the organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid, and stearic acid.
[0021] In some embodiments, the heating temperature of the single heating reaction is 35-55° C., and the reaction time is 1-3 hours.
[0022] In some embodiments, the freeze-drying freezing temperature is -60 to -40°C, and the freezing time is 24 to 48 hours.
[0023] Finally, an embodiment of the present application also provides a battery pack, comprising a plurality of battery cells, wherein the thermal insulation material of any of the above embodiments is provided between the battery cells.
[0024] The present application provides a thermal insulation material, including cellulose aerogel and an organic phase change material dispersed in the cellulose aerogel; wherein the cellulose aerogel is obtained by reacting bacterial cellulose with a crosslinking agent. The thermal insulation material provided by the present application greatly improves the pore size of the cellulose aerogel by modifying the bacterial cellulose aerogel with a crosslinking agent, and uses this as a supporting material for the organic phase change material to prepare a thermal insulation material with ultra-high energy storage efficiency, which can be used between battery cells when the heat generation of the single battery cell is too high, effectively absorbing heat, and preventing the battery cells from spreading due to direct heat conduction between the modules. The present application provides a method for preparing a thermal insulation material, which is used to prepare the thermal insulation material in any of the above embodiments, comprising the following steps: providing bacterial cellulose and a crosslinking agent, mixing, heating and reacting to obtain a homogenate; freeze-drying the homogenate to obtain a cellulose aerogel; immersing the cellulose aerogel in an organic phase change material liquid to obtain a thermal insulation material. A cellulose aerogel with a good pore structure is prepared by a freeze-drying process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.
[0026] Figure 1 A schematic diagram of a method for preparing a thermal insulation material provided in an embodiment of the present application;
[0027] Figure 2 A schematic diagram of the reaction principle between bacterial cellulose and a cross-linking agent in a thermal insulation material provided in Example 1 of the present application;
[0028] Figure 3 This is a performance test result diagram of the cellulose aerogel provided in Example 1 of the present application and the aerogel provided in Comparative Example 1;
[0029] Figure 4 This is a performance test result diagram of the thermal insulation material provided in Example 1 of the present application and the thermal insulation material provided in Comparative Example 1. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0031] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more features.
[0032] The disclosure below provides many different embodiments or examples to realize the different structures of the present application. In order to simplify the disclosure of the present application, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present application.
[0033] The first embodiment of the present application provides a thermal insulation material, including cellulose aerogel and an organic phase change material dispersed in the cellulose aerogel; wherein the cellulose aerogel is obtained by reacting bacterial cellulose with a cross-linking agent.
[0034] Phase change material, also known as solid-liquid phase change material, is a material that can achieve solid-liquid phase change within a specific temperature range. When the temperature rises to its melting point, the phase change material will quickly change from solid to liquid, absorbing a large amount of heat to complete the phase change; when the temperature drops, the phase change will quickly change from liquid to solid, releasing the previously absorbed heat to achieve energy storage and temperature control. Since there is a risk of material leakage when the organic phase change material is in liquid state, cellulose aerogel is used as a carrier with a rich porous structure, which can disperse the organic phase change material in the pores inside it, making the organic phase change material stable.
[0035] By using a cross-linking agent to modify the bacterial cellulose aerogel, the pore size of the cellulose aerogel is greatly improved. This is used as a supporting material for an organic phase change material to prepare an insulating material with ultra-high energy storage efficiency. It can be used between battery cells to effectively absorb heat when the heat generated by a single battery cell is too high.
[0036] In some embodiments, the average pore size of the cellulose aerogel is 18 to 23 nm. It is understood that the average pore size of the cellulose aerogel (unit: nm) can be any value of 18, 19, 20, 21, 22, 23 or a range between any two values. When the pore size of the cellulose aerogel meets the above value range, the organic phase change material can be blocked in the pores inside the cellulose aerogel to the maximum extent, thereby avoiding leakage of the organic phase change material.
[0037] In some embodiments, the melting point of the organic phase change material is 10-20° C. It is understandable that the melting point of the organic phase change material (unit: ° C) can be any value of 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range between any two values. When the melting point of the organic phase change material meets the above value range, it can ensure that the formed thermal insulation material has relatively ideal performance in terms of both thermal insulation durability and response rate.
[0038] In some embodiments, the mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:(2-5).
[0039] In some embodiments, the molecular weight of the bacterial cellulose is 50,000 to 2,000,000.
[0040] It is understood that the molecular weight of bacterial cellulose can be any value of 50000, 100000, 500000, 1000000, 1500000, 2000000 or a range between any two values. When the molecular weight of bacterial cellulose satisfies the above range, the formed cellulose aerogel has more appropriate pores and better mechanical strength.
[0041] In some embodiments, the cross-linking agent includes at least one of glutaraldehyde, malondialdehyde, and glyoxal.
[0042] In some embodiments, the organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid, and stearic acid.
[0043] The second embodiment of the present application provides a method for preparing a thermal insulation material, which is used to prepare the thermal insulation material in any of the above embodiments, see Figure 1 , including the following steps:
[0044] Providing bacterial cellulose and a cross-linking agent, mixing, heating and reacting to obtain a homogenate;
[0045] The homogenate is freeze-dried to obtain cellulose aerogel;
[0046] The cellulose aerogel is immersed in an organic phase change material liquid to obtain a thermal insulation material.
[0047] Specifically, the preparation method of the thermal insulation material provided in this embodiment can be achieved through the following steps:
[0048] S1, placing bacterial cellulose homogenate and a cross-linking agent in a beaker, adding hydrochloric acid as a catalyst, heating and stirring in a constant temperature stirrer for a certain period of time, uniformly dispersing the cross-linking agent in the bacterial cellulose homogenate and performing a cross-linking reaction on the bacterial cellulose to obtain a homogenate;
[0049] S2, removing unreacted cross-linking agent and bubbles from the homogenate, placing it in a beaker, placing it in a cold well for pre-freezing, and then freeze-drying it for a certain period of time to obtain a modified cellulose aerogel;
[0050] S3. The cellulose aerogel prepared as above is placed in a dryer for vacuum treatment to remove the air in the cellulose aerogel, thereby enhancing the adsorption capacity of the cellulose aerogel for oleic acid. The cellulose aerogel is then immersed in liquid oleic acid and vacuum impregnated in a vacuum drying oven. The obtained product is then placed on oil-absorbing paper to remove excess organic phase change material, until no oil marks are observed on the oil-absorbing paper, and then stored in a refrigerator to obtain the final thermal insulation material.
[0051] During the reaction of the cross-linking agent and bacterial cellulose, the reactive functional groups at both ends of the cross-linking agent, such as dialdehyde or diamine, can undergo condensation reaction with the hydroxyl groups on the bacterial cellulose to achieve cross-linking with the bacterial cellulose, thereby strengthening the 3D network of the bacterial cellulose aerogel.
[0052] In some embodiments, the volume ratio of bacterial cellulose slurry to cross-linking agent is 50:(1-2.5).
[0053] It is understandable that the volume ratio of the bacterial cellulose slurry to the cross-linking agent can be any value of 50:1, 50:1.5, 50:2, 50:2.5 or a range between any two values. When the volume ratio of the bacterial cellulose slurry to the cross-linking agent meets the above range, it can ensure that the cellulose aerogel finally formed has a reasonable pore size, and thus can block the organic phase change material in the pores inside the cellulose aerogel to the maximum extent, thereby avoiding leakage of the organic phase change material.
[0054] In some embodiments, the mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:(2-5).
[0055] It is understandable that the mass ratio of the cellulose aerogel slurry to the organic phase change material can be any value of 2:2, 2:3, 2:4, 2:5 or a range between any two values. When the mass ratio of the cellulose aerogel slurry to the organic phase change material satisfies the above value range, the formed thermal insulation material has a higher energy storage efficiency and better mechanical strength.
[0056] In some embodiments, the cross-linking agent includes at least one of glutaraldehyde, malondialdehyde, and glyoxal.
[0057] See also Figure 2 Dialdehyde cross-linking agents represented by glutaraldehyde can undergo aldol condensation reaction with the hydroxyl groups on bacterial cellulose. The hydroxyl groups generated after the reaction are unstable and will continue to react with the hydroxyl groups of bacterial cellulose until a grid-like polymer is formed, which has a more significant effect on strengthening the 3D network structure of bacterial cellulose.
[0058] In some embodiments, the organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid, and stearic acid.
[0059] In some embodiments, the heating temperature of a single heating reaction is 35-55° C., and the reaction time is 1-3 hours.
[0060] It can be understood that the value of the heating temperature of the single heating reaction (unit: ° C) can be any value of 53, 40, 45, 50, 55 or a range between any two values; the value of the reaction time (unit: h) can be any value of 1, 1.5, 2, 2.5, 3 or a range between any two values. When the conditions of the heating reaction meet the above range of values, the reacting bacterial cellulose and the cross-linking agent can fully undergo a cross-linking reaction to form a uniform cross-linked product.
[0061] In some embodiments, the freezing temperature of freeze-drying is -60 to -40°C, and the freezing time is 24 to 48 hours.
[0062] It can be understood that the value of the freezing temperature of freeze drying (unit: ° C) can be any value among -60, -55, -50, -45, -40 or a range between any two values; the value of the freezing time (unit: h) can be any value among 24, 36, 48 or a range between any two values. When the freeze drying conditions meet the above range of values, a stable cellulose aerogel can be formed.
[0063] A third embodiment of the present application provides a battery pack, comprising the thermal insulation material of any of the above embodiments.
[0064] The following is a description of the thermal insulation material and battery pack provided by the present application in conjunction with specific embodiments:
[0065] Example 1
[0066] Example 1 provides a heat insulation material, see Figure 1 Prepared by:
[0067] S1. Place 28ml bacterial cellulose homogenate and 0.6ml glutaraldehyde in a 50ml beaker, add 0.1ml hydrochloric acid as a catalyst, heat and stir in a 70℃ constant temperature stirrer for 6 hours, and evenly disperse glutaraldehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10g of the homogenate, centrifuge the homogenate using a centrifuge to remove unreacted glutaraldehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2h, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0068] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -60 °C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel. The reaction mechanism of glutaraldehyde and bacterial cellulose is as follows: Figure 2 The average pore size of cellulose aerogel was calculated using the BJH adsorption model and the result was 18.1 nm.
[0069] S3. Select oleic acid as the organic phase change material. First, place the prepared cellulose aerogel in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel, strengthen the adsorption capacity of cellulose aerogel for oleic acid, and then immerse the aerogel in 15g of liquid oleic acid in a vacuum drying oven at 40°C for vacuum impregnation. First, adsorb under vacuum for 1 hour, turn the sample over, then adsorb under normal pressure for 0.5 hours, turn the sample over, and repeat the above operation three times to achieve the purpose of adsorbing as much oleic acid as possible into the pores of the cellulose aerogel. Place the obtained phase change insulation material on oil-absorbing paper for at least 48 hours to remove excess oleic acid, until no oil print is observed on the oil-absorbing paper, and then store it in a refrigerator to obtain an insulation material.
[0070] Example 2
[0071] S1. Place 28ml bacterial cellulose homogenate and 0.6ml glutaraldehyde in a 50ml beaker, add 0.1ml hydrochloric acid as a catalyst, heat and stir in a 70℃ constant temperature stirrer for 6 hours, and evenly disperse glutaraldehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10g of the homogenate, centrifuge the homogenate using a centrifuge to remove unreacted glutaraldehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2h, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0072] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -60°C for pre-freezing for 12 h, and finally freeze-dry it for 24 h to obtain cellulose aerogel.
[0073] S3. Lauric acid was selected as the organic phase change material. The cellulose aerogel prepared above was placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel. Then the aerogel was immersed in 15g of liquid lauric acid in a vacuum drying oven at 35°C for vacuum impregnation. First, adsorb under vacuum for 0.5h, turn the sample over, then adsorb under normal pressure for 0.5h, turn the sample over, and repeat the above operation three times.
[0074] Example 3
[0075] S1. Place 28ml bacterial cellulose homogenate and 1.5ml glutaraldehyde in a 50ml beaker, add 0.1ml hydrochloric acid as a catalyst, heat and stir in a 70℃ constant temperature stirrer for 6 hours, and evenly disperse glutaraldehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10g of homogenate, centrifuge the homogenate using a centrifuge to remove unreacted glutaraldehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2h, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0076] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -60°C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel.
[0077] S3. Palmitic acid was selected as the organic phase change material. The cellulose aerogel prepared above was first placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel. Then the aerogel was immersed in 10g of liquid palmitic acid in a vacuum drying oven at 40°C for vacuum impregnation. First, adsorb under vacuum for 1 hour, turn the sample over, then adsorb under normal pressure for 1 hour, turn the sample over, and repeat the above operation three times.
[0078] Example 4
[0079] S1. Place 28ml bacterial cellulose homogenate and 0.6ml glutaraldehyde in a 50ml beaker, add 0.1ml hydrochloric acid as a catalyst, heat and stir in a 70℃ constant temperature stirrer for 6 hours, and evenly disperse glutaraldehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10g of the homogenate, centrifuge the homogenate using a centrifuge to remove unreacted glutaraldehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2h, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0080] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -40°C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel.
[0081] S3. Select fatty acid as the organic phase change material, first place the prepared cellulose aerogel in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel, and then immerse the aerogel in 15g of liquid fatty acid in a vacuum drying oven at 55°C for vacuum impregnation. First adsorb under vacuum for 1 hour, turn the sample over, then adsorb under normal pressure for 0.5 hours, turn the sample over, and repeat the above operation three times.
[0082] Example 5
[0083] S1. Place 28 ml of bacterial cellulose homogenate and 0.6 ml of malondialdehyde in a 50 ml beaker, add 0.1 ml of hydrochloric acid as a catalyst, heat and stir in a 70 ° C constant temperature stirrer for 6 hours, and evenly disperse the malondialdehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10 g of the homogenate, centrifuge the homogenate using a centrifuge to remove unreacted malondialdehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2 hours, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0084] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -40°C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel.
[0085] S3. Lauric acid was selected as the organic phase change material. The cellulose aerogel prepared above was placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel. Then the aerogel was immersed in 25g of liquid lauric acid in a vacuum drying oven at 40°C for vacuum impregnation. First, adsorb under vacuum for 1.5 hours, turn the sample over, and then adsorb under normal pressure for 1.5 hours, turn the sample over, and repeat the above operation three times.
[0086] Example 6
[0087] S1. Place 28ml bacterial cellulose homogenate and 0.6ml glyoxal in a 50ml beaker, add 0.1ml hydrochloric acid as a catalyst, heat and stir in a 70℃ constant temperature stirrer for 6 hours, and evenly disperse glyoxal in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10g of homogenate, centrifuge the homogenate to remove unreacted glyoxal. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2h, ultrasonicate for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0088] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -60°C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel.
[0089] S3. Oleic acid is selected as the organic phase change material. The cellulose aerogel prepared above is first placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel. Then the aerogel is immersed in 15g of liquid oleic acid in a vacuum drying oven at 40°C for vacuum impregnation. First, adsorb under vacuum for 1 hour, turn the sample over, then adsorb under normal pressure for 0.5 hours, turn the sample over, and repeat the above operation three times.
[0090] The preparation methods of the thermal insulation materials in Examples 2 to 6 are consistent with those in Example 1, with only the reaction raw materials and reaction parameters being adjusted.
[0091] Comparative Example 1
[0092] Comparative Example 1 provides a thermal insulation material, which is prepared in the following manner:
[0093] S1. Pure cellulose aerogel is provided. The average pore size of the cellulose aerogel is calculated using the BJH adsorption model, and the result is 25.6 nm.
[0094] S2. Oleic acid is selected as the organic phase change material. The cellulose aerogel prepared above is first placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel, and the adsorption capacity of the cellulose aerogel for oleic acid is enhanced. Then the aerogel is immersed in 15g of liquid oleic acid in a vacuum drying oven at 40°C for vacuum impregnation. First, adsorb under vacuum for 1 hour, turn the sample over, then adsorb under normal pressure for 0.5 hours, turn the sample over, and repeat the above operation three times to achieve the purpose of adsorbing as much oleic acid as possible into the pores of the cellulose aerogel. The obtained phase change insulation material is placed on oil-absorbing paper for at least 48 hours to remove excess oleic acid until no oil print is observed on the oil-absorbing paper, and then placed in a refrigerator for storage to obtain an insulation material.
[0095] Comparative Example 2
[0096] Comparative Example 2 provides a thermal insulation material, which is prepared in the following manner:
[0097] S1. Pure cellulose aerogel is provided. The average pore size of the cellulose aerogel is calculated using the BJH adsorption model, and the result is 26.7 nm.
[0098] S2. Lauric acid was selected as the organic phase change material. The cellulose aerogel prepared above was first placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel and enhance the adsorption capacity of the cellulose aerogel for lauric acid. The aerogel was then immersed in 5g of liquid lauric acid in a vacuum drying oven at 55°C for vacuum impregnation. First, the sample was adsorbed under vacuum for 2.5 hours, and then turned over. Then, the sample was adsorbed under normal pressure for 2.5 hours, and then turned over. The above operation was repeated three times.
[0099] Comparative Example 3
[0100] Comparative Example 3 provides a thermal insulation material, which is prepared in the following manner:
[0101] S1. Place 28 ml of bacterial cellulose homogenate and 2 ml of valeraldehyde in a 50 ml beaker, add 0.1 ml of hydrochloric acid as a catalyst, heat and stir in a 70 ° C constant temperature stirrer for 6 hours, and evenly disperse the valeraldehyde in the bacterial cellulose homogenate and cross-link with the bacterial cellulose. After stirring, weigh 10 g of homogenate, centrifuge the homogenate using a centrifuge to remove unreacted valeraldehyde. Then add ultrapure water to restore the original weight and stir on a magnetic stirrer for 2 hours, ultrasonically apply for half an hour, and evenly disperse the bacterial cellulose in the homogenate to improve the agglomeration of bacterial cellulose. Then use a dryer to vacuum the homogenate to remove bubbles in the homogenate to prevent residual bubbles from affecting the pore structure of the aerogel.
[0102] S2. Weigh 10 g of the homogenate after degassing into a 25 ml beaker, place it in a cold well at -60°C for pre-freezing for 12 h, and finally freeze-dry for 48 h to obtain cellulose aerogel.
[0103] S3. Palmitic acid is selected as the organic phase change material. The cellulose aerogel prepared above is placed in a dryer for vacuum treatment for 5 minutes to remove the air in the cellulose aerogel and enhance the adsorption capacity of the cellulose aerogel for palmitic acid. The aerogel is then immersed in 5g of liquid palmitic acid in a vacuum drying oven at 60°C for vacuum impregnation. First, adsorb under vacuum for 0.5h, turn the sample over, then adsorb under normal pressure for 0.5h, turn the sample over, and repeat the above operation three times.
[0104] The preparation methods of the thermal insulation materials in Comparative Examples 2 to 3 are consistent with those in Example 1, with only the reaction raw materials and reaction parameters being adjusted.
[0105] The reaction raw materials and thermal conductivity results in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] It can be seen from Table 1 that when the cellulose aerogel in the thermal insulation material does not contain a cross-linking agent, the average pore size of the aerogel will be larger. It can be seen from Comparative Example 3 that when too much cross-linking agent is used, the average pore size of the aerogel will also be larger.
[0110] Figure 3 The nitrogen adsorption and desorption curves of the cellulose aerogel in Example 1 and the aerogel in Comparative Example 1 and the distribution diagram of mesopores and micropores are shown. The adsorption / desorption isotherms of the aerogels are obtained by a BET surface area analyzer (microActive for ASAP 2460 2.02). The micropore and mesopore distributions are obtained by the Horvath-Kawazoe (HK) and Barrett-Joyner-Halenda (BJH) methods, respectively. Figure 3 It can be seen that both aerogels have type IV isotherms and typical H3-type hysteresis loops, indicating that the aerogel has a mesoporous structure with slit pores. When P / P0>0.9, the isotherm curve rises significantly, and no platform is observed, indicating that there are macropores in the aerogel. The cellulose aerogel in Example 1 has more micropores and mesopores than the aerogel in Comparative Example 1, and the pore volume of the micropores and mesopores is greatly increased. This is because the added glutaraldehyde uses the aldehyde group to react with the abundant hydroxyl groups on the bacterial cellulose to form a hemiacetal reaction, and uses a chemical bond stronger than the hydrogen bond to connect the two ends of the glutaraldehyde to the bacterial cellulose, thereby strengthening the 3D network structure of the aerogel and protecting more pore structures during the freeze-drying process. At the same time, the connected glutaraldehyde plays the role of dividing the holes, dividing a large hole into two or more smaller holes.
[0111] like Figure 4 The figure shows the thermal conductivity of two aerogels measured by a high-temperature thermal conductivity meter (TC-3200). The thermal conductivity of the cellulose aerogel modified by glutaraldehyde is significantly lower than that of the pure bacterial cellulose aerogel, from 32.5mW / m·K of the pure aerogel to 28.9mW / m·K, and the thermal insulation performance is enhanced. This is because the added glutaraldehyde cross-links with the bacterial cellulose to change the network structure of the bacterial cellulose aerogel, and the network structure of the aerogel is extremely important for the excellent thermal insulation performance of the aerogel.
[0112] Table 2 shows the thermal performance parameters and heat storage efficiency test results of the pure phase change material and the composite phase change material in Example 1 and Comparative Example 1 using a differential scanning calorimeter (DSC 214, Netzsch) at a heating rate of 5°C·min-1.
[0113] Table 2
[0114]
[0115] As shown in Table 2, the melting enthalpy of the thermal insulation material in Comparative Example 1 is 83.3 J / g, and the heat storage efficiency reaches 91.8%. In Example 1, the melting enthalpy of the thermal insulation material modified by glutaraldehyde is increased to 88.0 J / g, and the heat storage efficiency is increased to 97.1%. This result shows that the loading capacity of oleic acid of the modified BCW prepared in Example 1 is significantly stronger than that of the unmodified BCA. This is because the addition of glutaraldehyde strengthens the pore structure of the aerogel, better resists the oppression of the capillary force during the freeze-drying process, retains more pore structures, and provides more sites or spaces for loading oleic acid. At the same time, the aerogel modified by glutaraldehyde reduces the pore size of the pores in the process of strengthening the pore structure, and the capillary force to prevent oleic acid from leaking is enhanced, so that oleic acid is better blocked in the pores rich in aerogel.
[0116] The above is a detailed introduction to a thermal insulation material and a battery pack provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A thermal insulation material, characterized in that: It comprises cellulose aerogel and an organic phase change material dispersed in the cellulose aerogel; wherein the cellulose aerogel is obtained by reacting bacterial cellulose with a crosslinking agent.
2. A thermal insulation material according to claim 1, characterized in that: The average pore diameter of the cellulose aerogel is 18-23 nm.
3. A thermal insulation material according to claim 1, characterized in that: The melting point of the organic phase change material is 10-20°C.
4. A thermal insulation material according to claim 1, characterized in that: The mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:(2-5).
5. A thermal insulation material according to claim 1, characterized in that: The molecular weight of the bacterial cellulose is 50,000 to 2,000,000.
6. A thermal insulation material according to claim 1, characterized in that: The cross-linking agent includes at least one of glutaraldehyde, malondialdehyde and glyoxal; The organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid and stearic acid.
7. A method for preparing a thermal insulation material according to any one of claims 1 to 6, characterized in that: The steps include: The bacterial cellulose and the cross-linking agent are mixed and heated to react to obtain a homogenate; freeze-drying the homogenate to obtain cellulose aerogel; The cellulose aerogel is immersed in an organic phase change material liquid to obtain the thermal insulation material.
8. The method for preparing a thermal insulation material according to claim 7, characterized in that: The volume ratio of the bacterial cellulose slurry to the cross-linking agent is 50:(1-2.5); The mass ratio of the cellulose aerogel slurry to the organic phase change material is 2:(2-5); The cross-linking agent includes at least one of glutaraldehyde, malondialdehyde and glyoxal; The organic phase change material includes at least one of oleic acid, lauric acid, palmitic acid and stearic acid.
9. The method for preparing a thermal insulation material according to claim 7, characterized in that: The heating temperature of the heating reaction is 35-55°C, and the reaction time is 1-3h; The freezing temperature of the freeze-drying is -60 to -40°C, and the freezing time is 24 to 48 hours.
10. A battery pack, comprising a plurality of battery cells, characterized in that: The battery cells include the thermal insulation material as described in any one of claims 1 to 6 or the thermal insulation material prepared by the preparation method as described in any one of claims 7 to 9.
Citation Information
Cited By
Preparation method of silicon-based aerogel composite phase change material heat insulation felt
CN121975495A